Digitalisasi Pemetaan Usaha Pandai Besi di Dusun 12 Benteng Rejo: Upaya Peningkatan Visibilitas UMKM Melalui UMKM - Namira Hamni Lubis; Anggi Rizkina Sari Siregar; Selfi Okta Rahmadini; Fitriani Fitriani (Universitas 45 Surabaya, 2025)
This study aims to analyze the process and impact of business mapping digitalization for blacksmith enterprises in Dusun 12 Benteng Rejo as an effort to increase the visibility of Micro, Small, and Medium Enterprises (MSMEs) through the Google Maps platform. The study is motivated by the condition of blacksmith craftsmen who still rely on traditional promotion and have not yet adopted digital technology. The research uses a qualitative approach with field studies, direct observation, and interviews with local entrepreneurs. Data were analyzed descriptively to illustrate conditions before and after the implementation of digitalization. The results show that digitalization through registration in Google Business Profile and location mapping on Google Maps had a significant effect on improving visibility and customer reach. Twelve blacksmith enterprises were successfully registered and can now be accessed publicly through online search. After the digitalization process, orders increased by approximately 40%, supported by positive customer reviews and better product documentation. Moreover, this initiative improved local digital literacy and encouraged collaboration among blacksmiths. This study concludes that location-based digitalization is a strategic step to empower rural economies. Digital mapping serves not only as a promotional tool but also as a means to strengthen local identity and create a sustainable business ecosystem.